Mortality and Clinical Interventions in Critically ill Patient With Coronavirus Disease 2019: A Systematic Review and Meta-Analysis - Qian, Zhicheng; Lu, Shuya; Luo, Xufei; Chen, Yaolong; Liu, Ling (Frontiers in Medicine, 2021)
Objective: The aims of this systematic review and meta-analysis were to summarize the current existing evidence on outcome of critically ill patients with COVID-19, as well as to evaluate the effectiveness of clinical interventions. Data Sources: We searched MEDLINE, the Cochrane library, Web of Science, China Biology Medicine disc (CBM), China National Knowledge Infrastructure (CNKI), and Wanfang Data from their inception to May 15, 2021. Search strings consisted of various search terms related to the concepts of mortality of critically ill patients and clinical interventions. Study Selection: After eliminating duplicates, two reviewers independently screened all titles and abstracts first, and then the full-texts of potentially relevant articles were reviewed to identify cohort study and case series that focus on mortality of critically ill patients and clinical interventions. Main Outcomes and Measures: The primary outcome was the mortality of critically ill patients with COVID-19. The secondary outcomes included all sorts of supportive care Results: 27 cohort studies and 6 case series involving 42219 participants met our inclusion criteria. All-cause mortality in ICU was 35% and mortality in hospital was 32% in critically ill patients with COVID-19 for the year 2020 with very high between-study heterogeneity (I2=97%; p<0.01). In subgroup analysis mortality during ICU hospitalization in China was 39%, in Asia except for China was 48%, in Europe was 34%, in America was 15%, in Middle East was 39%. Non-survived patients who had older age (−8.10, 95%CI [−9.31 to −6.90]), a higher APACHE II score (−4.90, 95%CI [−6.54 to −3.27]), a higher SOFA score (−2.27, 95%CI [−2.95 to −1.59]) and a lower PaO2/FiO2 ratio (34.77, 95%CI [14.68 to 54.85]) than those who survived. Among clinical interventions, IMV with RR 0.49, 95%CI [0.39 to 0.61], KRT (RR 0.34, 95%CI [0.26 to 0.43]) and vasopressor (RR 0.54, 95%CI [0.34 to 0.88]) used more in survived patients. Conclusions: Mortality was high in critically ill patients with COVID-19 based on low-quality evidence and regional difference existed. Early identification of critical characteristics and use of support care help to indicate the outcome of critically ill patients. Key Words: Mortality; Critically ill patients; COVID-19; Clinical interventions; Supportive care